Mergulhão Bot: Design and Prototyping of a Low-Cost Hybrid Vehicle for Oil Leakage Detection - Oliveira, Guilherme C. De; Garcia, Enrique F.; Santos, Julio Cesar S. Dos; Pedroso, Adir A.; Pereira, Leonardo C.; Drews, Paulo L. J. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2023: Anais do XV Simpósio Brasileiro de Robótica e XX Simpósio Latino Americano de Robótica, 2023)
Unmanned vehicles are increasingly popular and their demand increases annually. Since their invention in the 1950s, these vehicles have been widely used in various applications which include environmental monitoring. Oil spill in the oceans is an example of a serious problem for marine ecosystems that can be investigated with these vehicles. Currently, government authorities are analyzing satellite images to detect oil spots, but when oil submerges in the ocean becomes imperceptible by satellites. This oil can be silently moving to coastal regions, without containment maneuvers. Unmanned vehicles may be an effective alternative to remote sensing in these cases. In this scenario, this work presents a new design of a hybrid vehicle to move on the ocean surface and be able to submerge water, called the Mergulhão Bot. The robot was mechanically modeled using OnShape software, simulations were performed using ROS, Gazebo, and the UUV Simulator package.